2008
DOI: 10.1111/j.1463-1326.2007.00827.x
|View full text |Cite
|
Sign up to set email alerts
|

Preglomerular and postglomerular basal diameter changes and reactivity to angiotensin II in obese rats

Abstract: Our data indicate that in obese rats, a vasodilated state in small preglomerular microvessels and a vasoconstricted state in the postglomerular arterioles exist. Although AngII cancelled the former, the latter remained. Therefore, these data reveal periglomerular vascular changes that may play a role in glomerular dysfunction and renal pathology associated with obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This leads to an increase of the hydrostatic pressure in the glomerular capillaries, which contributes to an elevated GFR and albuminuria. However, it has been shown that ANG II can exaggerate the vasoconstriction response of the efferent arteriole in obese rats, favoring glomerular dysfunction (49). In our study, since losartan, an AT 1 angiotensin receptor antagonist, prevents the increased GFR and restores the cortical blood flow, we might hypothesize that ANG II acts through the AT 1 receptor, which has been demonstrated to be distributed on renal efferent arteriole (17,29).…”
Section: Discussionmentioning
confidence: 64%
“…This leads to an increase of the hydrostatic pressure in the glomerular capillaries, which contributes to an elevated GFR and albuminuria. However, it has been shown that ANG II can exaggerate the vasoconstriction response of the efferent arteriole in obese rats, favoring glomerular dysfunction (49). In our study, since losartan, an AT 1 angiotensin receptor antagonist, prevents the increased GFR and restores the cortical blood flow, we might hypothesize that ANG II acts through the AT 1 receptor, which has been demonstrated to be distributed on renal efferent arteriole (17,29).…”
Section: Discussionmentioning
confidence: 64%
“…In young patients with T1D and hyperfiltration and in patients with type 2 diabetes (T2D), abnormalities in both R A and R E have been reported (20,26). Less, however, is known about the effect of exogenous ANGII on renal segmental resistance changes in humans, which may depend on a variety of clinical factors, including age (27) and weight (28). In this set of mechanistic studies, our first major observation was that, in adults with T1D, DKD resistors had similar responses in RVR to RAAS…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] ARBs are known to dilate efferent arterioles more than afferent arterioles, and to improve glomerular hypertension because AT-1 receptors exist more abundantly in the former. 20 Reports on the nephro-protective effects of ARBs are diverse in methodology; [20][21][22][23][24][25][26][27] however, few studies have concentrated on the morphology of afferent and efferent arterioles. In this study, we examined the morphology of rat renal tissue and noted a marked improvement in glomerular lesions and tubular protein casts in the ZFR+ARB group.…”
Section: Discussionmentioning
confidence: 99%